Random Variate Generation with Formal Guarantees - Saad, Feras A.; Lee, Wonyeol (Proceedings of ACM on programming languages, 2025)
Generating random variates is a fundamental operation in diverse areas of computer science and is supported in almost all modern programming languages. Traditional software libraries for random variate generation are grounded in the idealized "Real-RAM" model of computation, where algorithms are assumed to be able to access uniformly distributed real numbers from the unit interval and compute with infinite-precision real arithmetic. These assumptions are unrealistic, as any software implementation of a Real-RAM algorithm on a physical computer can instead access a stream of individual random bits and computes with finite-precision arithmetic. As a result, existing libraries have few theoretical guarantees in practice. For example, the actual distribution of a random variate generator is generally unknown, intractable to quantify, and arbitrarily different from the desired distribution; causing runtime errors, unexpected behavior, and inconsistent APIs. This article introduces a new approach to principled and practical random variate generation with formal guarantees. The key idea is to first specify the desired probability distribution in terms of a finite-precision numerical program that defines its cumulative distribution function (CDF), and then generate exact random variates according to this CDF. We present a universal and fully automated method to synthesize exact random variate generators given any numerical CDF implemented in any binary number format, such as floating-point, fixed-point, and posits. The method is guaranteed to operate with the same precision used to specify the CDF, does not overflow, avoids expensive arbitrary-precision arithmetic, and exposes a consistent API. The method rests on a novel space-time optimal implementation for the class of generators that attain the information-theoretically optimal Knuth and Yao entropy rate, consuming the least possible number of input random bits per output variate. We develop a random variate generation library using our method in C and evaluate it on a diverse set of "continuous" and "discrete" distributions, showing competitive runtime with the state-of-the-art GNU Scientific Library while delivering higher accuracy, entropy efficiency, and automation.